Insulinotropic properties of whey protein hydrolysates and impact of peptide fractionation on insulinotropic response - Nongonierma, Alice; Gaudel, Celine; Murray, Brian; Flynn, Sarah; Kelly, Phillip; Newsholme, Philip; FitzGerald, Richard (Elsevier, 2013)
The influence of different substrates and the effect of pH regulation during enzymatic hydrolysis of whey protein on glucose-stimulated insulin secretion by BRIN-BD11 pancreatic beta cells were studied. No significant differences (P ≥ 0.05) were detected in terms of glucose-stimulated insulin secretion by BRIN-BD11 pancreatic beta cells exposed to whey protein hydrolysates (WPH1 and WPH2) obtained with two different whey protein substrates. The whey protein hydrolysate (WPH3) obtained without pH regulation during hydrolysis, had a significantly lower insulinotropic potential in BRIN-BD11 cells than the WPH1 hydrolysate that was manufactured with pH regulation. Fractionation of WPH1 was carried out to enrich bioactive peptides. Comparing the different fractionation techniques studied (solid-phase extraction and semi-preparative reverse phase-high performance liquid chromatography), the most potent insulinotropic fraction was enriched in free amino acids and contained relatively hydrophilic peptides. This indicates that amino acids and hydrophilic peptides may be involved in the insulinotropic effect of WPH1.